2020
DOI: 10.4103/aca.aca_138_19
|View full text |Cite
|
Sign up to set email alerts
|

Neurological dysfunction after cardiac surgery and cardiac intensive care admission: A narrative review part 1: The problem; nomenclature; delirium and postoperative neurocognitive disorder; and the role of cardiac surgery and anesthesia

Abstract: The association with cardiac surgery with cognitive decline was first reported in the 1960s after the introduction of coronary artery surgery. The incidence in cognitive decline was thought to be more after cardiac surgery, especially with the use of the cardiopulmonary bypass. Anesthesia and surgery are both associated with cognitive decline but many other factors appear to contribute its genesis. On-pump surgery, microembolization during manipulation of the heart and great vessels, temperature changes, pH ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…In our study, the incidence of new PND within 7 days after surgery was 33.33%. These statistics, despite being higher than the incidence rate after noncardiac surgery, are consistent with other research in cardiac surgery ( 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the incidence of new PND within 7 days after surgery was 33.33%. These statistics, despite being higher than the incidence rate after noncardiac surgery, are consistent with other research in cardiac surgery ( 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…Prior research indicated that cardiac surgery has been associated with higher rates of PND, a serious complication associated with high morbidity and mortality ( 38 ) and that the most promising pharmacological strategy to avoid this complication seemed to be perioperative administration of dexmedetomidine ( 9 , 39 ). In recent years, a great deal of research confirmed that dexmedetomidine had a protective effect on multiple organ systems, namely, the heart, lungs, kidneys, liver, and the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic cross-clamp time, CPB time, AF, and blood transfusions are the other factors which are thought to be implicated in the etiology of POND. [18][19][20][21][22][23] Operative strategies including single aortic clamp and care against aortic manipulation may reduce the risk for POND by decreasing microembolism. No-touch technique for proximal anastomoses, offpump surgery, and hybrid procedures can be reliable alternatives in patients with AC to prevent POND and overall mortality.…”
Section: Discussionmentioning
confidence: 99%